Congeners-Specific Intestinal Absorption Of Microcystins In An In Vitro 3D Human Intestinal Epithelium: The Role Of Influx/Efflux Transporters - Turco, Laura; Santori, Nicoletta; Buratti, Franca M.; Dorne, Jean-Lou C. M.; Testai, Emanuela (Frontiers in Toxicology, 2022)
Microcystins (MCs) constitute a group of over 200 variants and are increasingly considered as emerging toxins in food and feed safety, particularly with regards to sea-food and fish consumption. Toxicity of MCs is congener-specific, being characterised by different acute potencies, likely related to the differential activity of metabolic enzymes and transporters proteins involved in their cellular uptake. However, the active transport of MCs across intestinal membranes has not been fully elucidated. Our results, obtained using a fit for purpose 3D human reconstructed intestinal epithelium, provide new information on the complex mechanisms involved in the absorption of 5 MC variants’: it is indeed characterised by the equilibrium between uptake and extrusion, since the selected congeners are substrates of both influx and efflux proteins. In the range of tested nominal concentrations (10-40 µM) fully representative of relevant exposure scenarios, none of the active tested transporters were saturated. The comparison of permeability (Papp) values of MCs variants highlighted a dose independent relationship for MC-LR, -YR and -RR (Papp x 10-7 ranged from 2.95 to 3.54 cm2/sec), whereas -LW and –LF showed a dose dependent increase in permeability reaching Papp values which were similar to the other congeners at 40 µM. MC-RR, -LR, -YR show absorption values around 5% of the administered dose. Due to their lipophilicity, MC-LW and -LF were also detected within the cellular compartment. The intestinal uptake was only partially attributable to OATPs, suggesting the involvement of additional transporters. Regarding the efflux proteins, MCs are not P-gp substrates whereas MRP2 and to a lesser extent BCRP are active in their extrusion. Despite the presence of GST proteins, as an indication of metabolic competence, in the intestinal tissue, MC-conjugates were never detected in our experimental settings.